Splenomegaly development and disseminated intravascular coagulation syndrome in acute canine babesiosis - O. A. Dubova; D. V. Feshchenko; T. I. Bakhur; A. A. Dubovyi; O. A. Zghozinska; I. V. Chala (Regulatory Mechanisms in Biosystems, 2021)
Disseminated intravascular coagulation (DIC) syndrome is the main defining process in the pathogenetic axis of complications in canine babesiosis. The involvement of the spleen with further irreversible changes in the organ largely determines the severity of the animal’s condition after spontaneous babesiosis. The work presented here aimed to determine the role of the DIC syndrome as a triggering factor for lesions of the spleen. Clinical and laboratory studies (haematological, biochemical, hemodynamic) have been carried out. Pathological studies of the removed spleen were carried out by histological methods using universal and specific staining. After suffering acute spontaneous babesiosis, the development of hypersplenism and splenomegaly was found in dogs. The diagnosis was confirmed haematologically by the detected cytopenia, normochromic type anaemia. An additional parameter was a significantly increased erythrocyte sedimentation rate. The biochemical profile indicated the development of bilirubinaemia due to the conjugated fraction, hyperfermentation of transaminases, hypoalbuminemia, which reflected the development of hepatitis and liver failure. Markers of DIC syndrome in laboratory studies are represented by reliable hypofibrinogenemia, increased level of fibrinogen/fibrin degradation products, including D-dimer, and soluble fibrin monomer complexes. The multidirectional indices of coagulation tests (activated partial thromboplastin and prothrombin time) made it possible to classify the stage of “consumption coagulopathy” of the DIC syndrome. The haemodynamic parameters of the sick dogs were characterized by a significant deficit in the circulating blood volume. Together with the indicators of the “consumption coagulopathy” stage of the DIC syndrome, the hemodynamic indexes indicate a moderate degree of shock stage II – the stable reversibility, but the magnitude of the circulating blood volume deficit determines the tendency towards shock irreversibility. Histological studies have established a significant proliferation of the stromal elements of the organ, the formation of specific complexes of vessels with sinuses, clogging with blood clots, and the organ's parenchyma dystrophy. Such changes characterize complete splenomegaly, which is based on the organo-pathology of the DIC syndrome. The deposition of “old” fibrin in the connective tissue structures of the spleen indicates that DIC syndrome continues throughout the entire period of hyperplastic changes in the organ. The presence of hyalinosis in blood vessel walls of the spleen parenchyma determines irreversible changes in them. Thus, DIC syndrome is the basis for splenomegaly development in dogs after acute spontaneous babesiosis. It is confirmed by laboratory blood tests and histologically by the presence of fibrin thrombi in the structures of the organ, which determine the organopathology of the syndrome. The information obtained serves to expand the concepts of the pathogenesis of blood protozoal disease, define the high risk of complications that can become fatal for the health and life of animals.